Influence of Turkish origin on hematology reference intervals in the German population - Mayr, Franz Xaver; Bertram, Alexander; Cario, Holger; Frühwald, Michael C.; Groß, Hans Jürgen; Groening, Arndt; Grützner, Stefanie; Gscheidmeier, Thomas; Hoffmann, Reinhard; Krebs, Alexander; Ruf, Hans Georg; Torge, Antje; et al. (Scientific Reports, 2021)
Reference intervals for laboratory test results have to be appropriate for the population in which they are used to be clinically useful. While sex and age are established partitioning criteria, patients’ origin also influences laboratory test results, but is not commonly considered when creating or applying reference intervals. In the German population, stratification for ethnicity is rarely performed, and no ethnicity-specific hematology reference intervals have been reported yet. In this retrospective study, we investigated whether specific reference intervals are warranted for the numerically largest group of non-German descent, individuals originating from Turkey. To this end, we analyzed 1,314,754 test results from 167,294 patients from six German centers. Using a name-based algorithm, 1.9% of patients were identified as originating from Turkey, in line with census data and the algorithm’s sensitivity. Reference intervals and their confidence intervals were calculated using an indirect data mining approach, and Turkish and non-Turkish reference limits overlapped completely or partially in nearly all analytes, regardless of age and sex, and only 5/144 (3.5%) subgroups’ reference limits showed no overlap. We therefore conclude that the current practice of using common reference intervals is appropriate and allows correct clinical decision-making in patients originating from Turkey.
CRIS-Team Scopus Importer:2021-11-05